Styloid Process Elongation, Shape and Calcification Pattern According to Age and Gender - Hamouda, Dr.Saleh; Elmehadwi, Dr.Huda; A.H. Mohamed, Dr.Khadiga (Libyan Journal of Dentistry, 2020)
Background: Styloid process (SP) is a slender pointed part of the temporal bone, which is closely related to the stylomastoid foramen. As many important neurovascular structures located near the tip of SP, the elongation or ossification of stylohyoid ligament may be associated with pain related to orofacial region known as Eagle’s syndrome. Aim of this study was to assess the prevalence of elongated SP, its morphology and calcification pattern on digital panoramic radiographs in patients attending the dental clinic of the University of Benghazi. Material and Methods: The digital panoramic radiographs with visible styloid processes of the studied group of patients were studied for their visibility, length and pattern of calcification. The length of styloid processes was measured in the radiograph and was considered elongated if that length exceeded 30 mm. The prevalence and pattern of elongation and calcification were determined according to Langlais classification. Results: Out of the 304 patients (164 are males and 140 are females) examined radiographically, the elongation of SP was detected in 156 (51.31%) of the patients. It was bilateral in 151 (96.79%) cases. There were no significant differences between males and females in regard to the length and shape of SP between in all age groups in both sexes, but the calcification pattern was significantly different between the age groups in both sexes. The outlined pattern of calcification of SP was the most prevalent especially in the younger age group (10-19 years), while the complete calcification pattern was most commonly detected in the older age group (≥ 60 years). Conclusion: elongated SP whether it is accompanied by pain symptoms or asymptomatic, can easily be detected on a digital panoramic radiograph and should be considered in the differential diagnosis of orofacial pain.